Two Rb-Sr Whole Rock Isochrons from Plutons In the Cobequid Highlands, Nova Scotia, Canada - Donohoe, H. V.; Keppie, J. Duncan; Halliday, A. N. (Atlantic Geoscience, 1986)
Two Rb-Sr Hhole rock isochrons have been obtained from plutons In the Cobequid Highlands of Nova Scotia: the Debert River and Hart Lake-Byers Lake Plutons. The undeformed, unfoilated Debert River Pluton yielded an age of 596± 70 Ma and an Initial 87Sr/88Sr ratio of 0.7059 ± 0.0007. This age places an upper age limit on the detonation recorded In the Folly River Schist (youngest unit of the Bass River Complex), the d I or I tic Frog Lake Pluton, and the sedimentary rocks immediately north and east of the Debert River Pluton. The Hart Lake-Byers Lake Pluton yielded anageof348±5Maandan Initial 87Sr/88Sr ratio of 0.7046 ± 0.0008. The similarity of this age to that of the adjacent felsic volcanics of the Byers Brook For nation suggests that they are comagmatic and confine that a Carboniferous igneous event forms an Important part of the geological history of the Cobequid Highlands. The Initial 87Sr/88Sr ratio and the blotite-hornblende content of the two granites suggest a mafic Igneous loner crustal source or possible untie component for the magma. RÉSUMÉ Les plutons de Debert River et Hart Lake-Byers Lake dans les monts Cobequld en Nouvel le-Écosse ont livre deux isochrones Rb-Sr de roche globale. Il déformé ni fellé, le pluton de Debert River a donné un âge de 596± 70 Ma et un rapport 87Sr/88Sr initial de 0.7059 ± 0.0007. Ceci place une limite supérieure sur l’âge de la déformation enregistrée dans le schiste de Folly River (L’unité la plus jeune du complexe de Bass River), le pluton diorltique de Frog Lake et dans les roches sédimentaires Jouxtant le pluton de Debert River au nord et à l’est. Le pluton de Hart Lake-Byers Lake à produit un âge de 348 ± 5 Ma et un rapport isotopique 87Sr/88Sr initial de 0.7046 ± 0.008. Cet âge, similaire à ceux des volcanites felslques adjacentes de la formation de Byers Brook, suggére qu’lis sent comagnatiques, signe evident qu’un épisode igné carbonifère forme l’un des faits majeurs de L’histoire géologique des monts Cobequid. Le rapport 87Sr/88Sr initial et la teneur en blotite et hornbIende de ces deux granites suggérent une genèse crustale profonde du magma avec une possible contribution mantellique. [Traduit par le journal]